Bell-bottom technique in iliac branch era: mid-term single stent graft performance - Gabriele Pagliariccio (CVIR Endovascular, 2020)
Abstract Background Endovascular abdominal aortic aneurysm repair (EVAR) is considered the primary option for abdominal aortic aneurysm but the management of concomitant wide or aneurysmal iliac arteries (CIAs) is still controversial. Methods We retrospectively evaluated mid-term results of patients receiving standard EVAR combined with bell-bottom technique (BBT) using Medtronic Endurant endograft between January 2009 and December 2018. Patients were followed up by CT scan performed 1 month after the procedure and by duplex ultrasound annually (with or without contrast medium) followed by CT scan in case of evolution. Results Seventy-one patients (67 males; mean age of 77,1 years) with abdominal aortic aneurysm and wide or aneurysmal common iliac artery (distal landing zone diameter up to 25 mm and length more than 20 mm) were treated with standard EVAR and BBT (107 limbs) using Endurant stent graft. The median aortic diameter was 56,1 mm (31.0-85.0). Technical success was obtained in 100%. Mean procedural time was of 100.1 min. No 30 days’ mortality, renal failure or limb ischaemia occurred. The median follow-up was of 36.56 months (1–136). 5-year aneurysm related mortality was not found. At 5 years, the number of all-cause deaths was seven. The freedom from secondary intervention was 91.6% at 5 years. Three patients (4.4%) were treated for iliac related complications at 5 years: internal iliac artery aneurysm, iliac obstruction, type 1b endoleak, all successfully treated by endovascular technique. Conclusions According with this study BBT using Endurant stent graft is effective and safe with good mid-term results, with low rate of iliac related complications and no aneurysm related mortality.